Insect histology : practical laboratory techniques - Barbosa, Pedro, 1944-; Berry, Deborah L., 1972-; Kary, Christina S., 1975- (Chichester, West Sussex ; Hoboken, NJ : Wiley/Blackwell, 2014)
This title is a much needed update of Barbosa's self-published Manual of Basic Techniques in Insect Histology. It is a laboratory manual of'traditional' and'modern' insect histology techniques, completely revised using cutting-edge methodology carried out today and includes new immunohistochemical techniques not previously looked at. Insect Histology is designed as a resource for student and professional researchers, in academia and industry, who require basic information on the procedures that are essential for the histological display of the tissues of insects and related organisms.
Problems of sclerotized chitin : softening insect cuticle -- Fixation -- Dehydration, clearing, and embedding -- Staining -- Immunohistochemical staining -- Use of genetic markers in insect histology -- Fluorescence -- Mounting -- Preparation of whole mounts -- Whole mount staining -- Preparation of insect tissues -- Preparation of genitalia, mouthparts, and other body parts -- Preparation of chromosomes -- Appendix : dissecting fluids and insect saline solutions.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Entomology -- Laboratory manuals; Histology -- Laboratory manuals; Entomology; Histology; SCIENCE / Life Sciences / Zoology / General; Histology; Laboratory manuals; Electronic books; Electronic books